Multi-layer graphene loaded cobalt nitrogen carbon monatomic catalyst for advanced oxidation process as well as preparation method and application of multi-layer graphene loaded cobalt nitrogen carbon monatomic catalyst
Through the asymmetric coordination structure and strong interaction of multi-layer graphene-supported cobalt nitrogen carbon single-atom catalyst (CoN3/rGO), the activity, stability and mass transfer efficiency of single-atom catalysts in advanced oxidation processes are solved, and the efficient activation of persulfate-forming oxidant is achieved, which improves pollutant degradation efficiency and catalyst stability.
Patent Information
- Application Number
- CN202510621590.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-15
- Publication Date
- 2025-08-22
AI Technical Summary
In the advanced oxidation process, existing single-atom catalysts have problems such as low active site density, low electron transfer rate, poor stability, single support function and low mass transfer efficiency, making it difficult to effectively activate persulfate to form high-efficiency oxidants.
A multi-layer graphene-supported cobalt nitrogen carbon single-atom catalyst (CoN3/rGO) was prepared by hydrothermal method to form an asymmetric coordination structure. Combined with a multi-layer graphene support, the electron fluidity and coordination structure around the active center were enhanced, high-density active sites were formed, and cobalt atoms were fixed through strong interaction with the graphene support through Co-N covalent bonds, and micro-nano-scale pores were constructed to promote pollutant enrichment.
It realizes efficient activation of persulfate-forming oxidant, significantly improves the efficiency of pollutant degradation, improves the stability and selectivity of the catalyst, and can maintain high activity within a wide pH range, reduces metal consumption and enhances the ability to enrich pollutants.
Smart Images

Figure CN120515461A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of catalysis technology, and in particular relates to a multilayer graphene-supported cobalt-nitrogen-carbon single-atom catalyst for advanced oxidation processes, a preparation method thereof, and applications thereof. Background Art
[0002] Advanced oxidation processes (AOPs) are one of the most popular water treatment technologies for organic pollutant degradation in recent years. Initially, AOPs relied on the in-situ generation of highly oxidizing hydroxyl radicals (·OH) to remove organic matter. As more and more oxidizing species were discovered, the active species produced in AOPs were expanded to include SO4 ·- 、O2 ·- , singlet oxygen ( 1 O2), high valent metal oxygen (HVMO), etc. The traditional Fenton reaction in AOPs is often limited by acidic conditions (pH = 2.0-4.0) and the instability of H2O2 in practical applications, which has led to the recent development of the sulfate radical (SO4 ·- The research on AOPs of SR-AOPs has attracted wide attention from academia and industry. ·- Has a long half-life (SO4 ·- , 30-40μs; ·OH, <1μs), higher oxidation potential (SO4 ·- , E0=2.5-3.1V; ·OH, E0=1.9-2.7V), and is less affected by pH value (pH=2.0-8.0). SO4 ·- It can usually be generated by activation with peroxymonosulfate (PMS). Therefore, the Fenton-like reaction system initiated by PMS activation is considered to be a promising water purification technology among AOPs.
[0003] Common PMS activation methods require the introduction of external energy and generate a limited number of ROS species. With the increasing complexity of pollutant systems and the emergence of a growing number of novel pollutant structures, this single and inefficient approach has become increasingly inadequate. Catalysis has long been a driving force in promoting and improving chemical reactions, lowering the energy barriers between reactants and enabling more efficient interactions. Consequently, catalysts have been introduced into PMS activation systems to achieve more efficient and selective ROS generation pathways at ambient temperature and pressure. Since the 21st century, the emergence of a growing number of novel nanomaterials has steadily increased the importance of heterogeneous catalysis. Nanomaterials, due to their significantly higher surface area than macroscopic materials, offer significant improvements in efficiency compared to traditional catalysis. Metal-based nanomaterials with variable chemical valence states and unoccupied orbitals, particularly those containing multivalent metals, have long been considered excellent PMS catalysts. These materials primarily include metal oxides, metal sulfides, metal nanoalloys, metal-organic frameworks, and single-atom materials. Currently, the addition of catalysts to activate PMS has become the most widely studied approach. Among the many new catalysts, single-atom catalysts (SACs) are currently one of the most cutting-edge ones. Their active components exist in the form of single atoms to maximize the utilization of active sites. Therefore, they have the advantages of low consumption, high activity, stability, and selectivity.
[0004] However, current SACs also have some shortcomings, such as: (1) low active site density and insufficient catalytic efficiency. In traditional SACs (such as Co-N4), metal atoms are fixed in a symmetrical coordination form, the exposure of active sites is limited, and the poor conductivity of the carrier leads to a low electron transfer rate, making it difficult to break through the oxidant activation efficiency. (2) Metal atoms are easily agglomerated or leached, and have poor stability. Single-atom active sites have weak binding forces with the carrier (such as physical adsorption or weak coordination), and are easily migrated, agglomerated, or dissolved in strong acid / alkaline or long-cycle reactions, causing catalyst deactivation and secondary pollution. (3) The carrier function is single and the mass transfer efficiency is low. Traditional carbon-based carriers (such as activated carbon and carbon nanotubes) lack hierarchical pore structures, have low pollutant mass transfer rates, and have insufficient active site utilization. Summary of the Invention
[0005] The invention provides a catalyst for an advanced oxidation process, wherein the catalyst is a multi-layer graphene-supported cobalt-nitrogen-carbon single-atom catalyst.
[0006] The present invention provides a method for preparing the above catalyst, comprising the following steps:
[0007] The reduced graphene oxide is dispersed in formamide and ultrasonically treated, and then a cobalt salt is added and ultrasonically treated; the mixed solution is then subjected to a hydrothermal reaction, and after the reaction is completed, the product is washed and dried to obtain a multilayer graphene-supported cobalt-nitrogen-carbon single-atom catalyst.
[0008] In the above preparation method, each raw material is selected from the following parts:
[0009] 0.05-5 parts of reduced graphene oxide, 10-300 parts of formamide, and 0.01-0.4 parts of cobalt salt;
[0010] When the component is a solid component, the portion number represents grams; when the component is a liquid component, the portion number represents milliliters; in actual application, the portion number can be enlarged or reduced proportionally.
[0011] In a specific embodiment, the raw materials are selected from the following parts:
[0012] 0.1 parts of reduced graphene oxide, 30 parts of formamide, and 0.04 parts of cobalt salt;
[0013] When the component is a solid component, the portion number represents grams; when the component is a liquid component, the portion number represents milliliters; in actual application, the portion number can be enlarged or reduced proportionally.
[0014] In the above preparation method, the cobalt salt is selected from one or more of Co(NO3)2·6H2O and CoCl3·6H2O.
[0015] In the above preparation method, the purpose of the ultrasonic treatment is to mix the components uniformly. The present invention does not impose any specific restrictions on this technical feature, as long as the corresponding technical effect can be achieved.
[0016] In the above preparation method, the conditions of the hydrothermal reaction are selected from: hydrothermal reaction at 160-200° C. for 10-24 hours; preferably: hydrothermal reaction at 180° C. for 12 hours.
[0017] The present invention provides application of the catalyst in persulfate activation or sewage treatment.
[0018] The present invention provides a catalytic membrane, which is prepared by loading CoN3 / rGO onto a polyvinylidene fluoride (PVDF) membrane.
[0019] The preparation method of the above-mentioned catalytic membrane comprises the following steps:
[0020] 0.01 g of CoN3 / rGO was dispersed in 50 mL of ultrapure water and ultrasonicated for 30 min to prepare a dispersion. The dispersion was then filtered using a PVDF filter membrane and naturally dried to obtain a CoN3 / rGO / PVDF catalytic membrane.
[0021] The present invention provides a sewage treatment method, which comprises adding a multilayer graphene-loaded cobalt-nitrogen-carbon single-atom catalyst and persulfate to sewage to achieve deep treatment of the sewage and improve the biodegradability of the sewage.
[0022] In the above sewage treatment method, the amount of the catalyst is selected from 0.025 to 5 g / L, preferably 0.05 g / L; the amount of the persulfate is selected from 0.075 to 15 g / L, preferably 0.15 g / L.
[0023] In practical applications, the dosage of catalyst and persulfate can be appropriately adjusted according to different water qualities.
[0024] The beneficial effects of the present invention are:
[0025] The present invention synthesizes a multilayer graphene-supported cobalt, nitrogen, and carbon single-atom catalyst (CoN3 / rGO) by a one-step hydrothermal method, which is simple and feasible. Compared with the traditional CoN4 catalyst, the introduction of the multilayer graphene carrier (rGO) can achieve the following effects: increase electron mobility and operation capacity, improve charge transfer efficiency; adjust the coordination structure around the active center, so that the reaction selectivity of the catalyst is greatly increased; enable the catalyst to achieve excellent results at a lower metal loading, thereby reducing metal consumption and increasing the stability of the catalyst for long-term use. At the same time, it can also reduce the addition of cobalt, enhance overall stability, reduce cobalt leaching, and rGO itself can enhance the enrichment of pollutants, thereby further improving the overall performance. In addition, the central electron density of the three-nitrogen coordination structure is higher, which ensures that it has a weak binding force with various coexisting anions in the environment, giving it good anti-interference properties. The catalyst has very excellent activation performance for persulfate (PMS). Bisphenol A (BPA), as the target pollutant, can be completely degraded within 5 minutes in the CoN3 / rGO / PMS system, and its kinetic constant (kapp) value is 1.25min -1 , significantly higher than the currently common cobalt-based catalysts. Furthermore, CoN3 / rGO exhibits remarkable stability and environmental adaptability. CoN3 / rGO can be combined with PVDF to form a CoN3 / rGO / PVDF catalytic membrane, further highlighting its potential in practical applications such as industrial wastewater treatment.
[0026] By constructing a "CoN3 asymmetric coordination-multilayer graphene carrier" synergistic system, the present invention achieves the following technical effects: (1) High-density active sites and efficient electron transfer; cobalt atoms in the CoN3 structure are embedded in the carbon nitride lattice in the form of tri-nitrogen coordination, forming an asymmetric electron-deficient center, combined with the metal-like conductivity of multilayer graphene, accelerating electron transfer. (2) Atomic-level anchoring and stability; the strong interaction effect between the Co-N covalent bond (bond energy > 400kJ / mol) and the graphene carrier and surface CoNC synergistically fixes Co atoms and inhibits migration and agglomeration; the multilayer graphene barrier resists acid and alkali corrosion. (3) Wide pH adaptation and non-radical path regulation; the uncoordinated nitrogen atoms of CoN3 dynamically adsorb H + / OH - , maintaining activity in a wide pH range (3-11); generating 1 O2 and high-valent cobalt oxide species (Co=O). (4) Hierarchical mass transfer channels and interface synergistic effects; multilayer graphene constructs micron-nanoscale pores to promote pollutant enrichment; the π-π conjugated system on the graphene surface and the d orbital of CoN3 form electron transfer channels, accelerating the continuous activation of PMS; the hydrophobic interface repels humic acid (HA), improving the utilization of active sites.
[0027] In summary, the present invention is expected to overcome the deficiencies of traditional symmetrical coordination catalysts in terms of activity, selectivity, stability, etc., further broaden the application scope of single-atom catalysts, and thus show good application prospects in the field of catalytic technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 SEM image of CoN3 / rGO (a), TEM image of CoN3 / rGO (b), interlayer spacing of CoN3 / rGO (c), AC-HAADF-STEM image of CoN3 / rGO (d), EDS-mapping image of CoN3 / rGO (e);
[0029] Figure 2 XRD spectra of CoN3 / rGO (a), Raman spectra of rGO, CoN3 and CoN3 / rGO (b);
[0030] Figure 3 FT-EXAFS spectrum of Co K-edge in CoN3 / rGO (a), fitting spectrum of EXAFS K-edge of Co in CoN3 / rGO in R space (b), fitting spectrum of EXAFS K-edge of Co in CoN3 / rGO in k space (c);
[0031] Figure 4The removal performance of bisphenol A by different systems (a); the reaction kinetic constants of bisphenol A by different systems (b); the decomposition rate of PMS by different systems (c);
[0032] Figure 5 Effect of PMS concentration on the performance of PMS activated by CoN3 / rGO (a); reaction rate constant of BPA degradation at different PMS concentrations (b); effect of catalyst dosage on the performance of PMS activated by CoN3 / rGO (c); reaction rate constant of BPA degradation at different catalyst dosages (d); effect of pH on the performance of PMS activated by CoN3 / rGO (e); reaction rate constant of BPA degradation at different pH (f);
[0033] Figure 6 Cobalt leaching of CoN3 / rGO / PMS system (a); Cyclic performance of CoN3 / rGO (b); Cobalt leaching after each cycle of CoN3 / rGO (c); Effect of different anions on BPA degradation of CoN3 / rGO / PMS system (d); Effect of different cations on BPA degradation of CoN3 / rGO / PMS system (e); Effect of different water quality on BPA degradation of CoN3 / rGO / PMS system (f);
[0034] Figure 7 Continuously operating device based on CoN3 / rGO / PVDF membrane (a, b); contact angle test results of CoN3 / rGO / PVDF membrane (c); cross-sectional SEM image of CoN3 / rGO / PVDF membrane (d); surface SEM image of CoN3 / rGO / PVDF membrane (e); surface EDS-mapping results of CoN3 / rGO / PVDF membrane (f); treatment effect of CoN3 / rGO / PVDF membrane on BPA in various water samples and leaching of cobalt element during the reaction process (g). DETAILED DESCRIPTION
[0035] In the present invention, the reduced graphene oxide comes from Shanxi Coal Chemistry Research Institute of the Chinese Academy of Sciences.
[0036] The other materials used in the present invention, unless otherwise stated, can be obtained through commercial channels. Unless otherwise specified, other terms used in the present invention generally have the meanings commonly understood by those of ordinary skill in the art. The present invention will be further described in detail below with reference to specific examples and data. The following examples are merely for illustration of the present invention and are not intended to limit the scope of the present invention in any way.
[0037] Example 1
[0038] The steps for preparing multilayer graphene-supported cobalt-nitrogen-carbon single-atom catalyst are as follows:
[0039] 0.1 g of reduced graphene oxide (rGO) was dispersed in 30 mL of formamide (FA) and sonicated for 0.5 h. Then, 0.04 g of Co(NO₃)₂·6H₂O was added and sonicated for 0.5 h to obtain a Co / rGO / FA solution (0.0046 mol / L). The solution was then transferred to a polytetrafluoroethylene reactor and hydrothermally reacted at 180°C for 12 h. The product was washed with deionized water, collected by centrifugation, and freeze-dried in a vacuum oven to obtain a multilayer graphene-supported cobalt, nitrogen, and carbon single-atom catalyst, named CoN₃ / rGO.
[0040] 1. Physical Characterization of Catalysts
[0041] The catalyst prepared in Example 1 was physically characterized by the following images, including SEM images, TEM images, interlayer spacing, AC-HAADF-STEM images, EDS-mapping images, XRD spectra, Raman spectra, FT-EXAFS spectra, etc.
[0042] The test results are as follows Figures 1 to 3 As shown; among them, Figure 1 In the figure, a is the SEM image of CoN3 / rGO, b is the TEM image of CoN3 / rGO, c is the interlayer spacing of CoN3 / rGO, d is the AC-HAADF-STEM image of CoN3 / rGO, and e is the EDS-mapping image of CoN3 / rGO; Figure 2 In the figure, a is the XRD spectrum of CoN3 / rGO, and b is the Raman spectrum of rGO, CoN3 and CoN3 / rGO; Figure 3 In the figure, Figure a is the FT-EXAFS spectrum of the K-edge of Co in CoN3 / rGO, Figure b is the fitting spectrum of the K-edge EXAFS of Co in CoN3 / rGO in R space, and Figure c is the fitting spectrum of the K-edge EXAFS of Co in CoN3 / rGO in k space.
[0043] Scanning electron microscope (SEM) images show that there is an obvious graphene wrinkle structure in CoN3 / rGO ( Figure 1 a). Transmission electron microscopy can observe obvious multilayer structure ( Figure 1 b), and the interlayer spacing was measured to be approximately 0.321 nm ( Figure 1 c). The distribution of cobalt atoms was detected using aberration-corrected high-angle annular dark-field scanning transmission electron microscopy (AC-HAADF-STEM). The obvious bright spots in the image are attributed to the dispersed Co single atoms ( Figure 1 d). Energy spectrum analysis shows that C, N, O, and Co elements are evenly distributed in the catalyst ( Figure 1 e).
[0044] The X-ray diffraction (XRD) pattern of CoN3 / rGO showed that no peaks related to cobalt species were observed, which preliminarily indicated that no cobalt nanoparticles or cobalt oxides were produced. At the same time, the (002) diffraction peak belonging to carbon species was observed ( Figure 2 a). The Raman spectrum shows obvious D-band peaks and G-band peaks, proving the graphite phase structure of the material and the presence of defects. Compared with the individual rGO and CoN3 materials, the composite material CoN3 / rGO has a higher degree of defect structure ( Figure 2 b).
[0045] Extended X-ray absorption fine grain structure (EXAFS) spectroscopy revealed that there was no Co-Co interaction in CoN3 / rGO, whereas Obvious Co-N can be observed at the Figure 3 a). EXAFS fitting results show that in the first shell of CoN3 / rGO, Co atoms are coordinated with three N atoms ( Figure 3 b and Figure 3 c).
[0046] 2. Bisphenol A degradation experiment
[0047] Batch degradation experiments were conducted in a 200 mL vessel with stirring at 500 rpm at room temperature. First, 2.5 mg of the catalyst was added to 50 mL of a 10 mg / L BPA solution (pH 6.2, unadjusted or unbuffered). 0.0075 g of PMS was then added to the solution, marking the start of the degradation reaction. The reaction solution was sampled at regular intervals. The sample was then filtered through a 0.22 μm membrane filter and mixed with 50 μL of a 150 mM Na₂S₂O₃ solution. BPA concentration was determined using high-performance liquid chromatography (HPLC, LC-20, Shimadzu) using a C₁₈ column (4.6 mm × 150 mm, 5 μm) and a UV-visible detector.
[0048] The bisphenol A degradation experiment evaluated the catalytic effect of CoN3 / rGO on PMS.
[0049] The test results are as follows Figure 4 As shown:
[0050] like Figure 4 As shown in a, CoN3 / rGO has almost no adsorption effect on BPA. When only PMS exists, BPA cannot be degraded, indicating that the contribution of adsorption and PMS self-decomposition can be ignored. In contrast, in the CoN3 / rGO / PMS system, BPA is completely degraded within 5 minutes, and its kinetic constant (k app ) value is 1.25min -1, which is much higher than other systems. In addition, the PMS residual concentrations in different catalytic systems are as follows Figure 4 As shown in Figure c, CoN3 / rGO can activate 74% of PMS within 10 minutes, with the highest PMS utilization rate. In the same time range, CoN3 and rGO can only decompose about 15-30% of PMS, which easily leads to the waste of oxidants.
[0051] 3. Bisphenol A degradation parameter optimization experiment
[0052] The optimal catalyst dosage was investigated by varying the initial catalyst concentration, with four dosage gradients of 25, 50, 75, and 100 mg / L. The optimal PMS dosage was also investigated by varying the initial PMS concentration, with four concentration gradients of 0.25, 0.5, 0.75, and 1.00 mM. To investigate the effect of initial pH, the initial pH of the BPA solution was adjusted to approximately 3.08, 5.13, 6.89, 9.20, and 10.90 using H2SO4 and NaOH. In all experiments, samples were taken at regular intervals and the BPA concentration was measured.
[0053] The test results are as follows Figure 5 As shown:
[0054] Figure 5 a and Figure 5 Figure b shows the effect of PMS concentration on activity. Within the 0.25-0.75 mM range, kobs initially increases and then stabilizes with increasing PMS concentration. When the PMS concentration reaches 1.00 mM, kobs decreases. This is likely due to the PMS concentration exceeding the maximum tolerance of the active site, and excessive PMS can self-scaveng ROS. Therefore, a reasonable PMS concentration favors ROS generation.
[0055] Depend on Figure 5 c and Figure 5 As shown in Figure d, the amount of catalyst is also an important factor. When the CoN3 / rGO dosage increases from 25 mg / L to 75 mg / L, a significant increase in kobs and degradation efficiency is observed. However, when it increases to 100 mg / L, this trend slows down, indicating that more catalyst can provide more active sites for PMS activation.
[0056] Depend on Figure 5 e and Figure 5 As shown in Figure 5, within the pH range of 3.0 to 11.0, the removal efficiency of PMS activated by CoN3 / rGO can reach almost 100% within 10 min, demonstrating that CoN3 / rGO has a wide pH adaptability.
[0057] 4. Environmental adaptability experiment of CoN3 / rGO
[0058] Regarding the cyclic stability of the material, after each degradation experiment, the used catalyst was collected by filtration and washed with water three times. The sample on the filtration membrane was then added back to the solution system of the next experiment after ultrasonic vibration. The BPA degradation experiment was repeated for a total of five cycles. Subsequently, the samples from each cycle were used to perform BPA degradation experiments to obtain the changes in the activity of the catalyst.
[0059] To investigate the metal leaching concentration of the material, interval sampling was carried out during the BPA degradation test, and the concentration of metal Co in the samples was detected using an atomic absorption spectrometer (GGX 920, Haiguang).
[0060] The study of the material's anti-interference ability is also divided into two parts. The first part mainly explores the interference of different anions, cations and humic substances in water. Before the degradation experiment, 10mM Cl - 、HCO3 - 、H2PO4 - 、NO3 - 、SO4 2- 、F - , Ca 2+ Mg 2+ 、Fe 3+ The second part mainly explored the interference of the actual water matrix. Degradation experiments were conducted using tap water, river water, hot spring water, and groundwater as solvents for BPA solutions, with sampling and testing at intervals under these conditions.
[0061] The test results are as follows Figure 6 As shown:
[0062] The Co leaching analysis of the entire degradation process showed that the Co leaching amount of CoN3 / rGO was much lower than the 1 mg / L surface water environmental quality standard of China, indicating that it has good environmental safety ( Figure 6 a). In addition, five cycle performance tests were conducted under the same conditions ( Figure 6 b) In the first three cycles, the removal rate of BPA remained above 95%. By the fourth cycle, the removal rate of bisphenol A began to decline. After each cycle, the leaching concentration of Co remained below the national standard ( Figure 6 c), indicating that CoN3 / rGO has strong cyclic stability. In addition, common cations, anions and natural humic acid substances have no obvious effect on the degradation efficiency of BPA in CoN3 / rGO / PMS, but H2PO 4- Reduced kobs, and Fe 3+ Improved kobs due to H2PO 4-With Co 2+ Complexation and Fe 3+ The catalytic effect of Figure 6 d~ Figure 6 e). The effects of actual water matrices were investigated using tap water, river water, spring water, and groundwater as the background. The removal rates of BPA in each water matrix were all above 95%. Figure 6 e). Therefore, CoN3 / rGO has excellent resistance to common aqueous interfering substances.
[0063] 5. Continuous operation experiment of CoN3 / rGO / PVDF catalytic membrane
[0064] A mixed solution containing 2 mg / L BPA and 0.15 g / L PMS was prepared using ultrapure water, groundwater, and surface water as solvents. This solution was passed through a CoN3 / rGO / PVDF catalytic membrane at a flow rate of 0.6 mL / min. Samples were taken at intervals over a specific timeframe to measure the BPA and metallic Co concentrations.
[0065] The CoN3 / rGO / PVDF catalytic membrane was prepared by the following method:
[0066] 0.01 g of CoN3 / rGO was dispersed in 50 mL of ultrapure water and ultrasonicated for 30 min to prepare a dispersion. The dispersion was then filtered using a PVDF filter membrane and naturally dried to obtain a CoN3 / rGO / PVDF catalytic membrane.
[0067] The test results are as follows Figure 7 As shown:
[0068] By loading CoN3 / rGO onto polyvinylidene fluoride (PVDF) membrane to build a continuous operation device, continuous flow experiments were conducted to explore its practical application potential ( Figure 7 a. Figure 7 b). Figure 7 As shown in c, the contact angle of CoN3 / rGO / PVDF membrane with water is 13.49°, which shows good hydrophilicity. This property contributes to the effective contact reaction between the catalyst and water-soluble pollutants. The surface and cross-sectional SEM images show that CoN3 / rGO is completely and tightly attached to the surface of the PVDF membrane ( Figure 7 d. Figure 7e). EDS-mapping results showed that the four elements C, N, O, and Co were evenly distributed on the membrane surface. A mixed solution containing 2 mg / L BPA and 1 mM PMS was passed through the catalytic membrane at a flow rate of 0.6 mL / min. During continuous operation for 33 hours, the BPA removal efficiency in the ultrapure water system was maintained at over 90% without the addition of PMS, while 100% removal was always maintained in the surface water and groundwater systems, indicating that the catalytic membrane system has the ability to continuously and efficiently generate ROS ( Figure 7 g). In addition, throughout the treatment process, the leaching concentration of Co in the CoN3 / rGO / PVDF membrane was always lower than the 1 mg / L specified by China's national surface water standard, demonstrating significant safety and stability.
[0069] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any other manner. Any person skilled in the art may utilize the above-disclosed technical content to modify or modify the present invention into equivalent embodiments. However, any simple modifications, equivalent variations, and modifications to the above embodiments that do not depart from the technical content of the present invention and are based on the technical essence of the present invention remain within the scope of protection of the present invention.
Claims
1. A catalyst for an advanced oxidation process, characterized in that The catalyst is a multi-layer graphene-supported cobalt, nitrogen and carbon single-atom catalyst.
2. The catalyst according to claim 1, characterized in that The preparation method of the catalyst comprises the following steps: The reduced graphene oxide is dispersed in formamide and ultrasonically treated, and then a cobalt salt is added and ultrasonically treated; the mixed solution is then subjected to a hydrothermal reaction, and after the reaction is completed, the product is washed and dried to obtain a multilayer graphene-supported cobalt-nitrogen-carbon single-atom catalyst.
3. The catalyst according to claim 2, characterized in that The raw materials are selected from the following parts: 0.05-5 parts of reduced graphene oxide, 10-300 parts of formamide, and 0.01-0.4 parts of cobalt salt.
4. The catalyst according to claim 2, characterized in that The cobalt salt is selected from one or more of Co(NO3)2·6H2O and CoCl3·6H2O.
5. The catalyst according to claim 2, characterized in that The conditions of the hydrothermal reaction are selected from: hydrothermal reaction at 160-200° C. for 10-24 hours.
6. Use of the catalyst according to any one of claims 1 to 5 in persulfate activation or sewage treatment.
7. A catalytic membrane, characterized in that: The catalytic membrane is prepared by loading the catalyst according to any one of claims 1 to 5 onto a polyvinylidene fluoride membrane.
8. The catalytic membrane according to claim 7, characterized in that The preparation method of the catalytic membrane comprises the following steps: 0.01 g of CoN3 / rGO was dispersed in 50 mL of ultrapure water and ultrasonicated for 30 min to prepare a dispersion. The dispersion was then filtered using a PVDF filter membrane and naturally dried to obtain a CoN3 / rGO / PVDF catalytic membrane.
9. A sewage treatment method, characterized in that: The catalyst described in any one of claims 1 to 5 and persulfate are added to sewage to achieve deep treatment of the sewage and improve the biodegradability of the sewage.
10. The sewage treatment method according to claim 9, characterized in that: The amount of the catalyst is selected from 0.025 to 5 g / L, and the amount of the persulfate is selected from 0.075 to 15 g / L.
Citation Information
Cited By
Double-chamber decoupling water treatment method and device based on graphite blanket loaded cobalt manganese oxide composite material
CN121554054A